Wedge Instability Model Improvement of Shield Tunnel Excavation Face under Inclined Surface - Zhikui Wang; Yuan Wang; Di Feng; Yulong Niu (Advances in Civil Engineering)
In the process of the underground tunnel excavation, a kind of geological condition Necking Region is often encountered. The ground surface inclines very fast, which also leads to the increase of Earth pressure on the excavation face. The determination of the excavation face support pressure is essential to solve the active Earth pressure when the shield passes through the Necking Region. In this paper, based on Horn’s wedge model, considering the influence of surface dip angle on excavation face support pressure, the traditional wedge model was improved. The analytical solution of the ultimate support pressure for the active failure of shield excavation face was derived. To evaluate the quality of the model, the theoretical model was compared with the ultimate bearing pressure of the horizontal surface test. The influence of the ultimate support pressure on the parameters of Nc, Nγ, and Nq was consistent with the results of finite element simulation and existing theories, which verified the rationality of the model. The stability of the excavation face of the Heyan road river crossing tunnel was analyzed by using the improved wedge model. The results show that the mud support pressure considering the slope angle was 36 kPa higher than that without considering the slope angle.